Tribute to Professor H. R. Mackintosh - Gardiner, T. W. (Scottish journal of theology, 1952)
It Was significant of H. R. Mackintosh and his whole theological position that he made his class for the preparation of sermons a part of his course in theology. He often declared that the test of theology is whether it will preach well. When we first heard it, it may not have carried conviction. But experience taught us how true it is.Professor Mackintosh considered that the task of theology was to assist the proclamation of the Gospel. In his eyes theology was not an academic study but a practical one, because the Gospel is not so much the explanation of life as the cure of its disorder. It was his duty as a theologian to explain and justify the doctrine of the Church. But he never forgot that it would be the duty of his students when they became ministers of the Church to translate that doctrine into proclamation and appeal. If such preaching carried conviction and strengthened faith, then the theology behind it would be justified. To take an example-he used to draw a distinction between the positive and negative sides of the doctrine of election. He argued that the positive form of the doctrine is a conviction of believing experience. It declares that faith rests upon the grace of God which was directed towards the believer before ever he responded to it, and that he can count upon it to sustain him to the end.